WORD-OF-MOUTH: THE KEY DRIVER BEHIND GEN Y’S BUYING TRENDS - Ima Ilyani Ibrahim; Nurwahida Fuad; Noor Amirah Kamaruddin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
In today’s digital landscape, online word-of-mouth (WOM) has emerged as a powerful influence on purchase decisions, especially among Generation Y through social media (Socmed). This study explores the impact of key factors—innovativeness, trust, social capital, and opinion leadership—on Gen Y’s buying behaviour. Surveying 230 respondents from Northern Higher Learning Institution in Malaysia, the analysis used correlation and multiple regressions, revealing significant relationships among the variables. The findings underscore the importance for marketers to craft distinctive and innovative marketing strategies to capture the interest of their target audience.